Intensitas dan Prevalensi Ektoparasit Ikan Nila (Oreochromis niloticus, Linnaeus 1758) pada kolam budidaya di Kecamatan Beutong, Kabupaten Nagan Raya - Abdan, Mu'amar; Sari, Indah Permata; Hardiansyah, Hardiansyah; Harun, Harun (MAHSEER: Jurnal Ilmu-Ilmu Perairan dan Perikanan, 2023)
Tilapia has become an important economic fish cultivated by the people of Indonesia in general. Parasitic infections in fish have caused many financial losses and the sustainability of cultivation efforts. Therefore, this study aims to analyze the prevalence and intensity of parasites in tilapia that are maintained in aquaculture ponds, especially in Nagan Raya Regency. The study was conducted from August until September 2022 at UPR Mina Mandiri with the Smeer Method. As many as 30 samples were checked macroscopically and microscopically in the UPR Mina Mandiri laboratory, Nagan Raya. The results of the study showed 4 (four) types of ectoparasites found, namely Trichodina sp., Gyrodactylus sp., Dactyrogylus sp., and Ichthyophthirius multifiliis based on the highest interval of the length of prevalence, it is found at a length of 120 -180 mm with a prevalence of 40 % and the intensity of 10 individuals per sample, this result higher than the fish size of 20-100 mm with a prevalence of 20 % and the intensity of 19 ind/e, This result has also aimed that the highest infection organs are found on the surface of the body and gills.